Pemberdayaan Masyarakat Desa Patumbak I Melalui Sosialisasi Pemanfaatan Jahe Merah Sebagai Tanaman Obat - Jamilah Nasution; Rahmiati, Rahmiati; Muhammad Yamin Siregar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Community empowerment is a key strategy in achieving sustainable development goals, particularly in rural areas rich in natural and cultural resources. Through empowerment, communities are granted access to knowledge, skills, and resources that enable them to manage and utilize these potentials optimally and sustainably. This community service activity aims to enhance public knowledge about the benefits of red ginger (Zingiber officinale var. rubrum), which is known for its medicinal and economic properties. This program was conducted in Desa Patumbak I using an interactive lecture method, followed by an active discussion with 30 participants, including village officials, hamlet leaders, and community members. The results showed a significant improvement in participants' knowledge and skills in processing red ginger into economically valuable products. The development of red ginger-based products is expected to foster the growth of sustainable small in Desa Patumbak I. Thus, this activity has the potential to increase community income through new economic opportunities and support broader social welfare.